أثر استخدام برنامج الومضة في تنمية قدرات التفكير الإبداعي لدى طلاب الصف العاشر بالمرحلة الثانوية في دولة الكويت - عازمي، رشيد راشد علي (Kulliyah of Education, International Islamic University Malaysia, 2016)
The study aims to identify the effectiveness of using the Creative Spark program in developing capabilities of creative thinking of students of secondary school level in Kuwait. To help reach this objective, the researcher established two main hypotheses which he later verified. The current study adopts the experimental design and used two groups namely experimental and control. The sample of the current study consists of 38 students who were chosen from the study's population of which 19 students represented the experimental group and another 19 represented the control group. It took 28 periods to teach the units in the Creative Spark program during the second semester of the academic year 2014-2015. The current study used two instruments to measure the extent of developing creative thinking namely Torrance tests for creative thinking capabilities tests and the Creative Spark training program. The statistical approaches the researcher used are Mann-Whitney U test, Wilcox on test and the SPSS. The study concluded that there are statistically significant differences among the two medians of the grades of the experimental and control groups in the post-experiment test in students' capabilities of fluency, flexibility and originality of the verbal creative thinking test. There are also statistically significant differences between the medians of the grades of the experimental group in the pre and post experiment tests in the capabilities of fluency, flexibility, and originality of the verbal creative thinking test in favor of the post experiment test. There were no statistically significant differences between the medians of the grades of the experimental and control groups in the post experiment test in the abilities of fluency, flexibility, and originality of the figural creative thinking test. Moreover, there were statistically significant differences in the detailing ability and statistically significant differences between the medians of the grades of the experimental group in the pre and post experiment tests in the ability of fluency, flexibility, and details of the figural creative thinking test in favor of the post experiment test. However, there were no statistically significant differences in the originality capability. Some educational applications were proposed to contribute for improving the educational process, and some future researches that are related to the topic of the current study have been proposed.